Determination of Joint Life Term Insurance Premium Reserves Using the Prospective Method Based on the Cox-Ingersoll-Ross (CIR) Stochastic Interest Rate Model (Jurnal Matematika, Statistika dan Komputasi, 2026)
Premium reserves are the minimum funds that insurance companies are required to set aside to guarantee the fulfillment of long-term contractual obligations to policyholders in the future. Good management of premium reserves is very important to maintain the financial stability of insurance companies. This study aims to determine the premium reserves for joint life term life insurance using a prospective method based on the CIR model stochastic interest rate. This study uses a literature review method, with calculations based on the 2019 Indonesian Mortality Table (TMI) and historical BI interest rate data for estimating CIR model parameters. The calculation results show that premium reserves tend to increase at the beginning of the period and decrease towards the end of the period. Compared to fixed interest rates, premium reserves using CIR model interest rates are higher in each period.
Keywords: Joint Life Term Insurance; Premium Reserves; Cox-Ingersol-Ross (CIR); Prospective Method